2018
DOI: 10.1038/s41388-018-0637-x
|View full text |Cite|
|
Sign up to set email alerts
|

An evolving story of the metastatic voyage of ovarian cancer cells: cellular and molecular orchestration of the adipose-rich metastatic microenvironment

Abstract: Metastasis is a complex multistep process that involves critical interactions between cancer cells and a variety of stromal components in the tumor microenvironment, which profoundly influence the different aspects of the metastatic cascade and organ tropism of disseminating cancer cells. Ovarian cancer is the most lethal gynecological malignancy and is characterized by peritoneal disseminated metastasis. Evidence has demonstrated that ovarian cancer possesses specific metastatic tropism for the adipose-rich o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
151
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(162 citation statements)
references
References 111 publications
(183 reference statements)
0
151
0
2
Order By: Relevance
“…32). In addition, ovarian cancer metastasizes preferentially to the adipose-rich omentum (33). Omental fat possesses a distinct lipidomic signature with several lipid groups, including TAGs, DAGs, and SMs, showing differences when compared with subcutaneous fat (34).…”
Section: Triacylglyceridesmentioning
confidence: 99%
“…32). In addition, ovarian cancer metastasizes preferentially to the adipose-rich omentum (33). Omental fat possesses a distinct lipidomic signature with several lipid groups, including TAGs, DAGs, and SMs, showing differences when compared with subcutaneous fat (34).…”
Section: Triacylglyceridesmentioning
confidence: 99%
“…This enables the tumor cells to avoid anoikis and acquire a more invasive phenotype. Macrophages have also been demonstrated to play an active role in the formation of spheroids [111]. The multicellular spheroids attach to the mesothelial cells using various cell adhesion molecules.…”
Section: Circulating Cancer Cells Form Clusters Through Tomo-and Hetementioning
confidence: 99%
“…Further, several human studies reported suggestive associations of ovarian cancer risk with total cholesterol (45) (positive) or HDL (inverse) (46). Additionally, evidence has demonstrated that ovarian cancer metastasizes preferentially to the adipose-rich omentum, a key player in the creation of the metastatic tumor microenvironment in the intraperitoneal cavity (47). Omental fat possess a distinct lipidomic signature with several lipid groups, including TAGs, DAGs, and SMs, showing differences when compared to subcutaneous fat (48).…”
Section: Triacylglyceridesmentioning
confidence: 99%
“…Darker red shades represent higher overlap and similarity. Metabolite modules correspond to the squares along the diagonal.metastasizes preferentially to the adipose-rich omentum, a key player in the creation of the metastatic tumor microenvironment in the intraperitoneal cavity(47). Omental fat possess a distinct lipidomic signature with several lipid groups, including TAGs, DAGs, and SMs, showing differences when compared to subcutaneous fat(48).…”
mentioning
confidence: 99%